Weaving Relationships in Secondary Schools - Felix Méndez, Yuridia; Cuevas Durán, Consuelo (Trabajo Social UNAM, 2016)
Every day we are faced with the challenge of intervening in a complex changing reality, and while at times we reduce this to specific problems, it is undeniable that one problematic situation leads us to intervening in a unit which includes interrelated subjects, contexts and problems. From our experience in Estudios de Opinión y Participación Social A.C. (Opinion Studies and Social Participation) EOPSAC we have been witnesses to this fact. Work which had begun with citizen safety in a community had led us to work on the culture of legality with young people in schools, and the route of our work has taken us to center our intervention now on school violence.